DAMPAK CALISTUNG TERHADAP PERKEMBANGAN EMOSI ANAK 5-6 TAHUN DI PAUD FADULLAH KID’S PEKANBARU - Putri Clawson; Ravida Roleza (P3M STKIP 'Aisyiyah Riau, 2020)
This study aims to see and analyze the impact of calistung on the emotional development of children aged 5-6 years in Fadillah Kid's PAUD Pekanbaru City. This type of research is qualitative. This research is located in Fadillah Kid's PAUD, Pekanbaru City. The choice of this location is based on the consideration that the problems studied are in this location. Based on the results of interviews and observations (observations) researchers in the field about the